Fiqh Al-Hadist tentang Hibah Ayah kepada Anak - Fauzi Saleh (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2010)
This study aims to look at the different angles of grants to children compared to other parties. This study used a qualitative approach by referring to and discussing the understanding of the hadiths about grants specifically related to giving to children. The results of the research are that, first, it is permissible for parents to take back their child's gift on the grounds that it does not cause tuhmah (prejudice) from other parties. Both parents give to children, justice must be felt. Second, if it is understood that there is something wrong in the gift, it is advisable to withdraw it and to consider further technical giving more precisely and fairly. Third, the child is part of the parents, one of the qualities to make it good is to return the property of the parents that was given to him if needed and that becomes part of birr al-walidan